R for programmers : mastering the tools - Zhang, Dan (CRC Press, 2016)
Unlike other books about R, written from the perspective of statistics, [this book] is written from the perspective of programmers, providing a channel for programmers with expertise in other programming languages to quickly understand R. The contents are divided into four sections. The first section consists of the basics of R, explaining the advantages of using R, the installation of different versions of R, and the 12 frequently used packages of R. This will help you understand the tool packages, time series packages, and performance monitoring packages of R quickly. The second section discusses the server of R, examining the communication between R and other programming languages and the application of R as servers. This will help you integrate R with other programing languages and implement the server application of R. The third section discusses databases and big data, covering the communication between R and various databases, as well as R's integration with Hadoop. This will help you integrate R with the underlying level of other databases and implement the processing of big data by R, based on Hadoop. The fourth section comprises the appendices, introducing the installation of Java, various databases, and Hadoop. Because this is a reference book, there is no special sequence for reading all the chapters. You can choose the chapters in which you have an interest. If you are new to R, and you wish to master R comprehensively, simply follow the chapters in sequence. -- Back cover.